Morphology of Fern Spores from Phu Phan National Park - Kittima Makgomol (Agriculture and Natural Resources, 2006)
Morphological characteristics of fern spores collected from Phu Phan National Park were examined using a scanning electron microscope and a light microscope. A total of 36 species of ferns, were studied. Two types of spores, monolete and trilete, are observed. Spore size ranged from 15 to 130 μm. Ceratopteris thalictroides (L.) Brongn. has the largest spores. The spore surface patterns vary from cristate, fold, granulate, perforate, reticulate, rugate, rugulate, tuberculate to verrucate. Some combinations of these patterns were also observed. A subequatorial flange is common in Pteris.